Current and future treatments for hepatocellular carcinoma - Schlachterman, Alexander (World journal of gastroenterology : WJG, 2015)
Hepatocellular carcinoma （HCC） represents a uniquechallenge for physicians and patients. There is nodefinitively curative treatment. Rather, many treatmentand management modalities exist with differingadvantages and disadvantages. Both current guidelinesand individual patient concerns must be taken intoaccount in order to properly manage HCC. In addition,quality of life issues are particularly complex in patientswith HCC and these concerns must also be factoredinto treatment strategies. Thus, considering all theoptions and their various pros and cons can quicklybecome complex for both clinicians and patients. In thisreview, we systematically discuss the current treatmentmodalities available for HCC, detailing relevant clinicaldata, risks and rewards and overall outcomes for eachapproach. Surgical options discussed include resection,transplantation and ablation. We also discuss theradiation modalities conformal radiotherapy, yttrium 90microspheres and proton and heavy ion radiotherapy.The biologic agent Sorafenib is discussed as a promisingnew approach, and recent clinical trials are reviewed.We then detail currently described molecular pathwaysimplicated in the initiation and progression of HCC, andwe explore the potential of each pathway as an avenuefor drug exploitation. We hope this comprehensiveand forward-looking review enables both clinicians andpatients to understand various options and therebymake more informed decisions regarding this disease.